VD_FINDINFO Jug / 2014 / 260 vom 23. Januar 2015 - VD Tribunal cantonal (2015)
RESPONSABILITÉ CAUSALE, TRAUMATISME CERVICAL, PRESCRIPTION, PERTE DE GAIN, INCAPACITÉ DE TRAVAIL | 41 CO, 45 CO, 46 CO, 47 CO, 60 al. 2 CO, 255a CPC, 3 CPC, 58 LCR, 61 LCR, 62 LCR, 65 LCR, 83 al. 1 LCR